Avoiding Unintended Bias: Strategies for Providing More Equitable Health Care - VAN RYN, MICHELLE (Minn Med, 2016)
Research shows that unintentional bias on the part of physicians can influence the way they treat patients from certain racial and ethnic groups. Most physicians are unaware that they hold such biases, which can unknowingly contribute to inequalities in health care delivery. This article explains why a person’s thoughts and behaviors may not align, and provides strategies for preventing implicit biases from interfering with patient care.